L'élaboration collective de cartes mentales, une démarche didactique structurante pour l'apprentissage du vivre-ensemble à l'école - Christophe Marsollier
Faced with the development of anti-social behaviour and violence, over the past 20 years, learning to live together has become a priority. The competences that come into play in the complex nature of this learning process can be classified under five pillars. Based on socio-constructivist conceptions, according to which the practice of democratic debates contributes to the construction of moral judgement in children and teenagers (Piaget, 1932, Xypas, 2003), we show how, in the light of analysis of practices carried out in a class of CM2 pupils, the elaboration of mind maps by the teacher and /or the pupils, during discussions of an educational nature, both structure and promote this approach to learning. Depending on the type of mind map used, the teacher can in particular: probe possible answers to a problem associated with school life, strengthen the pupils' effort to conceptualise the values and the implicit norms which come into play in different types of behaviour, facilitate the discernment of their experience and the development of their reasoning skills; and help them to question the meaning of their non verbal behaviour.